The Impact of The Green Human Resources on The Efficiency and Effectiveness of Employees on the Industrial Sector in Sudan - Al-Taher, Sana Jadallah Al-Sheikh; Abu Sen, Ahmed Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aims at identifying the orientation of the green human resources administration and its impact of the employee’s efficiency and effectiveness on the industrial sector in Sudan. To realize the objectives of the study, The analytical descriptive method was followed and the questionnaire was used as the main tool for collecting data from a non-probability sample comprised of total 330 employees. The response percentage to questionnaire was estimated 88%. The data was statistically analyzed and processed by AMOSV25 and the reliability of the model was tested by Alpha Corpnakh Test. The study concluded with some results such as there is a partial positive relationship found between the orientations of the green human resources administration and the efficiency and effectiveness of employees. The conclusions were discussed in comparison with the literature reviews and presented a number of proposals for future studies.